Shot/Countershot : Film Tradition and Women's Cinema. - Fischer, Lucy (Princeton University Press, 2014)
"Do films made by women comprise a 'counter-cinema' radically different from the dominant tradition? Feminist film critics contend that women filmmakers do present from a distinctive vision, or 'countershot, ' and Lucy Fischer argues persuasively for this view. In rich detail this book relates the idea of a counter-cinema to theories of intertextuality and locates it in the broad context of recent feminist film, literary, and art criticism. Fischer also employs an original critical model of the dialogue between women's cinema and film tradition in the very organization of the book. Each chapter discusses a theme or genre (such as the musical, the 'double, ' the myth of womanhood, and the figure of the actress), counterposing two or more works--from the feminist and from the dominant cinema. What emerges is a fascinating picture of a women's film tradition that not only addresses but reworks and remakes the mainstream cinema. Fischer successfully combines two main strains of feminist criticism: the deconstructive critique of the dominant culture from a feminist standpoint and the study of a feminist counterculture. Examining films from Persona and The Lady from Shanghai to Girlfriends and Sisters, or the Balance of Happiness, the book offers fresh interpretations of individual works and can, incidentally, serve as an introduction to the field of feminist film criticism."--JSTOR website (viewed March 7, 2017)
Keywords: Women in motion pictures.; Feminist films -- History and criticism.; Feminism and motion pictures.; Film criticism.; Intertextuality.; Femmes au cinéma.; Films féministes -- Histoire et critique.; Féminisme et cinéma.; Critique cinématographique.; Intertextualité.; PERFORMING ARTS -- Reference.; PERFORMING ARTS -- Film & Video -- General.; Feminism and motion pictures; Feminist films; Film criticism; Intertextuality; Women in motion pictures; Criticism, interpretation, etc.